Coach selections and the relative age effect in male youth ice hockey - Hancock, D. J.; Ste-Marie, D. M.; Young, B. W. (Research Quarterly for Exercise and Sport, 2013)
Relative age effects (RAEs; when relatively older children possess participation and performance advantages over relatively younger children) are frequent in male team sports. One possible explanation is that coaches select players based on physical attributes, which are more likely witnessed in relatively older athletes. Purpose: To determine if coach selections are responsible for RAEs by comparing RAEs in male players who played competitive versus noncompetitive ice hockey. Method: Using chi-square, we analyzed the birth dates of 147,991 male ice hockey players who were 5 to 17 years old. Players' birth dates were divided into four quartiles, beginning with January to March, which coincides with Hockey Canada's selection year. Results: There were strong RAEs (p < .001) when players were selected to competitive teams by coaches through a tryout system. On noncompetitive teams that did not have coach selections, there were strong RAEs (p < .001) from 5 to 8 years old, but not 9 to 17 years old. Conclusions: Although coaches might perpetuate RAEs, other influential social agents might include parents, which ought to be investigated in future research.